Older women's responses and decisions after a fall: The work of getting "back to normal". Issue 12 (1st December 2016) - Bergeron, Caroline D.; Friedman, Daniela B.; Messias, DeAnne K. Hilfinger; Spencer, S. Melinda; Miller, Susan C.
ABSTRACT: In this descriptive qualitative research, we examined older women's responses and decisions after experiencing a fall. Falls were unexpected, sudden events that heightened these women's awareness of their physical, emotional, spiritual, and social independence. Interviewees reported assessing personal, physical, and emotional needs; feeling burdened by the extra work; trying to get back to normal; seeking and obtaining assistance and spiritual support; avoiding specific people, objects, and places; planning ahead; and putting the fall out of mind. Consideration of older women's post-fall responses and decisions should be incorporated into fall prevention and management programs, services, and clinical recommendations.